PROSEDUR PEMBAYARAN BELANJA PEGAWAI ASN DAN NON ASN PADA UPTD PSDA WILAYAH SUNGAI CILIWUNG-CISADANE - Ane Merlian (2023)
This final project report discusses procedures for paying ASN and non-ASN personnel expenditures at the UPTD PSDA of the Ciliwung-Cisadane River Region. The UPTD PSDA of the Ciliwung-Cisadane River Basin is the Service Technical Implementation Unit at the West Java Province Water Resources Service. Personnel expenditure is compensation that must be paid to government employees, in government agencies there are differences between employees, namely employees of the State Civil Apparatus and employees of non-State Civil Apparatuses so that this final report aims to find out the differences between ASN and non-ASN employee spending procedures. At the UPTD PSDA of the Ciliwung-Cisadane River Region, for payment of employee expenditure, submit an application to the West Java Province Water Resources Service by simply making a recapitulation of salaries, while non-ASN make direct submissions by making Direct Payment Request Letters (SPP LS) and Statements of Absolute Accountability (SPTJM).